Starting Leaps of Change from the Village:: A Lesson Learned from the Saemaul Undong Movement - Irfan Ridwan Maksum; Hariyati, Desy; Lutfi, Achmad; Defny Holidin (Technium Social Sciences Journal, 2020)
Village autonomy carries along a demand for villages to become self-reliant through optimization of village development that is based on local values and resources. This paper aims at exploring village development within the framework of the Saemaul Undong movement in South Korea. This paper conducts a qualitative approach, and data are collected through in-depth interviews with some key persons related to Saemaul Undong. By conducting Saemaul Undong, the village development movement in South Korea covered three important aspects: improving environmental quality, increasing income, and improving the villagers’ mentality. Those three aspects became the main values in transforming rural areas of South Korea to have a better life by optimizing their resources. Freedom in deciding the village program even there was also a national development policy is one of the key success factors of the Saemaul Undong movement. The success of the implementation of the Movement spread to other countries in order to adopt the strategies and model from its country of origin.